Changes in brain morphology in patients with obstructive sleep apnoea. Issue 10 (22nd September 2010) - Morrell, M J; Jackson, M L; Twigg, G L; Ghiassi, R; McRobbie, D W; Quest, R A; Pardoe, H; Pell, G S; Abbott, D F; Rochford, P D; Jackson, G D; Pierce, R J; et al.
Abstract : Background: Obstructive sleep apnoea (OSA) is a common disease that leads to daytime sleepiness and cognitive impairment. Attempts to investigate changes in brain morphology that may underlie these impairments have led to conflicting conclusions. This study was undertaken to aim to resolve this confusion, and determine whether OSA is associated with changes in brain morphology in a large group of patients with OSA, using improved voxel-based morphometry analysis, an automated unbiased method of detecting local changes in brain structure. Methods: 60 patients with OSA (mean apnoea hypopnoea index 55 (95% CI 48 to 62) events/h, 3 women) and 60 non-apnoeic controls (mean apnoea hypopnoea index 4 (95% CI 3 to 5) events/h, 5 women) were studied. Subjects were imaged using T1-weighted 3-D structural MRI (69 subjects at 1.5 T, 51 subjects at 3 T). Differences in grey matter were investigated in the two groups, controlling for age, sex, site and intracranial volume. Dedicated cerebellar analysis was performed on a subset of 108 scans using a spatially unbiased infratentorial template. Results: Patients with OSA had a reduction in grey matter volume in the right middle temporal gyrus compared with non-apnoeic controls (p<0.05, corrected for topological false discovery rate across the entire brain). A reduction in grey matter was also seen within the cerebellum, maximal in the left lobe VIIIb close to XI, extending across the midline into the right lobe. Conclusion: These data show that OSA is associated with focal loss of grey matter that could contribute to cognitive decline. Specifically, lesions in the cerebellum may result in both motor dysfunction and working memory deficits, with downstream negative consequences on tasks such as driving.